2005
DOI: 10.1139/v05-168
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of the spontaneous, proton- and AlIII-catalysed hydrolysis of 1,5-anhydrocellobiitol — Models for cellulose depolymerization in paper aging and alkaline pulping, and a benchmark for cellulase efficiency

Abstract: The kinetics of the spontaneous, proton- and AlIII-catalysed hydrolyses of the C1—O4′ bond in 1,5-anhydrocellobiitol have been measured at elevated temperatures (125.0–220.0 °C). Data for the first two processes extrapolate to the expression k = (8.6 ± 2.1 × 10–16) + (1.4 ± 0.2 × 10–9-pH) s–1 at 25 °C. These room-temperature figures were used to model cellulose depolymerization by the af Ekenstam equation. The spontaneous process is too slow to contribute to loss of paper strength on aging, and even the acid-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Aluminum sulfate, often called "papermaker's alum," can be considered a major source of both Brønsted and Lewis acidity in many of the books and documents that are of greatest concern. The role of aluminum sulfate in papermaking, as well as its increased use after 1807 in combination with rosin for the hydrophobic sizing of paper has been previously reviewed (Wilson and Parks 1979;Barrett 1989;Gurnagul et al 1993;El-Saied et al 1998;Baty and Sinnott 2005). We elaborate on its peculiar role in paper degradation below.…”
Section: Catalysismentioning
confidence: 91%
See 2 more Smart Citations
“…Aluminum sulfate, often called "papermaker's alum," can be considered a major source of both Brønsted and Lewis acidity in many of the books and documents that are of greatest concern. The role of aluminum sulfate in papermaking, as well as its increased use after 1807 in combination with rosin for the hydrophobic sizing of paper has been previously reviewed (Wilson and Parks 1979;Barrett 1989;Gurnagul et al 1993;El-Saied et al 1998;Baty and Sinnott 2005). We elaborate on its peculiar role in paper degradation below.…”
Section: Catalysismentioning
confidence: 91%
“…uncatalyzed process, and suggested that this degradation may be relevant to paper-based heritage collections in some cases. Baty and Sinnott (2005) greatly expanded that study using an improved model compound that effectively modeled cellulose around the glycosidic linkage for steric and inductive effects and concluded that, while the mechanism should be highly significant to alkaline pulping, the uncatalyzed process is too slow at ambient (library) conditions to do significant damage. Therefore, cellulose hydrolysis must be practically expected to procede by a catalytic mechanism in paperbased heritage collections.…”
Section: Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…1.2.2 SCCO 2 treatment The scheme of the experimental device used for SCCO 2 treatment was described in our previous paper (Baty and Sinnott, 2005). Before deacidification, rolled paper samples (about 20 g) were cleaned by SCCO 2 at 35°C under 18-22 MPa for 30 min in order to remove some possible impurities such as dust, microbial metabolites, additives and paper degradation products.…”
Section: Experiments Methodsmentioning
confidence: 99%
“…CDs, even when kept in a safe environment do not last much longer. Special paper may survive 1,000 years, see for example, [3]. Script carved in stone may survive a very long time, maybe one million years if it is protected from erosion.…”
Section: Introductionmentioning
confidence: 99%